2015
DOI: 10.1111/1755-5922.12130
|View full text |Cite
|
Sign up to set email alerts
|

Is Foxglove Effective in Heart Failure?

Abstract: SUMMARYBackground: Digoxin is the oldest known treatment for heart failure (HF) and has been demonstrated to reduce admissions for worsening heart failure in a large randomized trial recruiting patients in sinus rhythm with heart failure and ejection fraction <45%. This study forms the basis for current international guidelines recommending that digoxin should be considered in patients with symptomatic HF despite optimal doses of angiotensin-converting enzyme inhibitors/angiotensin receptor blockers, b-blocker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 36 publications
0
7
0
3
Order By: Relevance
“…Digoxin can be safely used during pregnancy, but its role in the treatment of systolic heart failure is currently being debated. 48,49 Studies of new experimental therapies have thus far been equivocal or negative. A small 1999 nonrandomized study of 6 patients given intravenous immunoglobulin showed improvement compared with 11 historical control subjects, 50 but no further studies have been conducted.…”
Section: Treatment and Complicationsmentioning
confidence: 99%
“…Digoxin can be safely used during pregnancy, but its role in the treatment of systolic heart failure is currently being debated. 48,49 Studies of new experimental therapies have thus far been equivocal or negative. A small 1999 nonrandomized study of 6 patients given intravenous immunoglobulin showed improvement compared with 11 historical control subjects, 50 but no further studies have been conducted.…”
Section: Treatment and Complicationsmentioning
confidence: 99%
“…The net effect of digoxin therapy is 1) lengthening of the cardiac action potential causing slower heart rates, and 2) increasing intracellular calcium concentration leading to increased myocardial contractility. 12,[14][15][16] Digoxin also has autonomic effects, including inhibition of sympathetic nervous outflow and enhanced parasympathetic tone. Through its autonomic effects, digoxin decreases automaticity, prolongs the effective refractory period, and slows conduction velocity through the atrioventricular (AV) node.…”
Section: Discussionmentioning
confidence: 99%
“…to avoid promoting uterine activity, β-1-selective agents can be preferable. Digoxin may be safely used during pregnancy, but its role is currently being debated [55,56].…”
Section: Chronic Heart Failure Managementmentioning
confidence: 99%